2011
DOI: 10.3354/cr01041
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between the Arctic Oscillation and winter extreme precipitation over central-southern China

Abstract: In this study, we analyzed the relationship between the Arctic Oscillation (AO) and extreme precipitation events over China during boreal winters from 1954 to 2009. The extreme precipitation events are defined as those with daily precipitation above the 80th (or 90th) percentiles. The AO shows a significantly positive correlation with the frequency of extreme precipitation events over China during January to February. Of all 287 stations in China, 238 stations have positive correlation coefficients and 82 stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 27 publications
2
22
0
2
Order By: Relevance
“…The Northern Hemisphere Annular Mode Index, (also referred as Arctic Oscillation Index) reflects the Westerlies in middle latitude of Northern Hemisphere. Previous researches have detected the relationship between Arctic Oscillation (North Atlantic Oscillation) and precipitation variation (Scaife et al, 2008;Yadav et al, 2009;Hu and Feng, 2010;Mao et al, 2011). Statistically significant correlations between precipitation indices and Northern Hemisphere Annular Mode Index occur in wintertime, which indicates the precipitation extremes in this study area are related to the Arctic Oscillation.…”
Section: Discussionmentioning
confidence: 61%
“…The Northern Hemisphere Annular Mode Index, (also referred as Arctic Oscillation Index) reflects the Westerlies in middle latitude of Northern Hemisphere. Previous researches have detected the relationship between Arctic Oscillation (North Atlantic Oscillation) and precipitation variation (Scaife et al, 2008;Yadav et al, 2009;Hu and Feng, 2010;Mao et al, 2011). Statistically significant correlations between precipitation indices and Northern Hemisphere Annular Mode Index occur in wintertime, which indicates the precipitation extremes in this study area are related to the Arctic Oscillation.…”
Section: Discussionmentioning
confidence: 61%
“…In this study, we have only analysed the links between limited circulation features of SST/Ts and U850 with the long‐term changes in precipitation. Other circulation factors such as the Arctic Oscillation (AO), PDO, and AMO also contribute to the long‐term precipitation trend over China (Li et al , ; Ma, ; Zhou et al , ; Mao et al , ; Qian and Zhou, ; Qian et al , ). However, the changes in circulation factors are not independent, which may often be mutually adjusted and connected corresponding to the global warming phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Mao et al . [] also showed that a positive AO usually induces significant winter extreme precipitation over central southern China through a stronger Middle East jet stream and deepened southern branch trough over the Bay of Bengal.…”
Section: Introductionmentioning
confidence: 99%